Human Milk Archaea Associated with Neonatal Gut Colonization and Its Co-Occurrence with Bacteria - Maricarmen Salas-López; Juan Manuel Vélez-Ixta; Diana Laura Rojas-Guerrero; Alberto Piña-Escobedo; José Manuel Hernández-Hernández; Martín Noé Rangel-Calvillo; Claudia Pérez-Cruz; Karina Corona-Cervantes; Carmen Josefina Juárez-Castelán; Jaime García-Mena (Microorganisms)
Archaea have been identified as early colonizers of the human intestine, appearing from the first days of life. It is hypothesized that the origin of many of these archaea is through vertical transmission during breastfeeding. In this study, we aimed to characterize the archaeal composition in samples of mother-neonate pairs to observe the potential vertical transmission. We performed a cross-sectional study characterizing the archaeal diversity of 40 human colostrum-neonatal stool samples by next-generation sequencing of V5–V6 16S rDNA libraries. Intra- and inter-sample analyses were carried out to describe the Archaeal diversity in each sample type. Human colostrum and neonatal stools presented similar core microbiota, mainly composed of the methanogens Methanoculleus and Methanosarcina. Beta diversity and metabolic prediction results suggest homogeneity between sample types. Further, the co-occurrence network analysis showed associations between Archaea and Bacteria, which might be relevant for these organisms’ presence in the human milk and neonatal stool ecosystems. According to relative abundance proportions, beta diversity, and co-occurrence analyses, the similarities found imply that there is vertical transmission of archaea through breastfeeding. Nonetheless, differential abundances between the sample types suggest other relevant sources for colonizing archaea to the neonatal gut.